2018
DOI: 10.1017/s0024282918000324
|View full text |Cite
|
Sign up to set email alerts
|

Calicioid diversity in humid inland British Columbia may increase into the 5th century after stand initiation

Abstract: Maintenance of biodiversity in managed forested landscapes requires detailed knowledge of the ecological requirements of specialist organisms linked to key microhabitats. Here we examine the relationship of 37 lichenized and unlichenized epiphytic calicioid species to stand age and substratum type in seven pairs of mid-seral (70–165 y) and old (220–470 y) forest stands in humid east-central British Columbia. Based on our inventory of eight host tree species, total calicioid diversity and mean species richness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 51 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Many North American studies have already identified the microhabitats of specific taxa, for example lichens and fungi (e.g., Goward and Arsenault, 2018), arthropods (e.g., Schowalter, 2017), or birds and mammals (e.g., Drapeau et al, 2009). Similarly, tree defect surveys are regularly used in certain regions of North America to describe forest stand quality and partially capture the TreM concept (Martin and Raymond, 2019).…”
Section: Benefits In Expanding the Trem Concept: An Example In North ...mentioning
confidence: 99%
“…Many North American studies have already identified the microhabitats of specific taxa, for example lichens and fungi (e.g., Goward and Arsenault, 2018), arthropods (e.g., Schowalter, 2017), or birds and mammals (e.g., Drapeau et al, 2009). Similarly, tree defect surveys are regularly used in certain regions of North America to describe forest stand quality and partially capture the TreM concept (Martin and Raymond, 2019).…”
Section: Benefits In Expanding the Trem Concept: An Example In North ...mentioning
confidence: 99%
“…In the index, the presence of 16 or more calicioid species is considered an indication of an “ancient” forest with a long history of continuity – and we found 16 calicioid species on Calvert Island. Goward and Arsenault (2018) also show that calicioid numbers positively correspond with stand age in the humid inland forests of British Columbia. We found Pseudocyphellaria rainierensis on Calvert Island as well, which is known to be restricted to old-growth forests in the British Columbia coastal region ( COSEWIC 2010 , Environment and Climate Change Canada 2017 ).…”
Section: Discussionmentioning
confidence: 66%
“… Pettersson et al (1995) , Hansell (1996) , Webber et al (2022) , Miranda-González et al (2023) ). Moreover, lichen communities are used as indicators of atmospheric pollution ( Hawksworth and Rose 1970 , Richardson 1988 , McMullin et al 2016 , McMullin et al 2017a ), ecological continuity ( Tibell 1992 , Selva 2003 , Goward and Arsenault 2018 , Bell-Doyon et al 2021 , Wiersma and McMullin 2022 ) and biodiversity conservation value ( Goward 1994 , Malíček et al 2019 , Miller et al 2020 ). Lichens are also numerous; in Canada and the United States alone, there are 5823 species in 805 genera, including allied fungi ( Esslinger 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The historical explanation pertains to the relatively recent development of the Caribou rainforest ecosystems. Palynological evidence suggests that Western Red-cedar, a tree whose presence can promote establishment of many old growth lichens (Goward & Arsenault 2018), entered the Caribou rainforest about 6,000 years ago in the extreme south and only 2,000 years ago farther north (Gavin et al 2009). This timeline is relevant insofar as dispersal in U.…”
Section: R a F Tmentioning
confidence: 99%